Clarifying misconceptions about compassionate care. (28th November 2013) - Dewar, Belinda; Adamson, Elizabeth; Smith, Stephen; Surfleet, Joyce; King, Linda
Abstract Aim To discuss the meaning of compassionate care as it applies to staff, patients and families in health and social care settings, its application to practice and how organizational infrastructures affect the delivery of care. Background The term compassion has assumed headline status and inclusion in current health and social care policy. Clarity of what the term means in practice is needed and may help to promote delivery of compassionate care consistently across health and social care settings. Design Discussion paper. Data Sources This article draws on data from an action research programme (Leadership in Compassionate Care Programme, 2007–2011) that focused on embedding compassionate care into practice and education and related literature focused on compassionate person‐centred care. A literature search was conducted and articles published in English relating to the terms compassionate, person‐centred care between 1999–2011 were included. Discussion Perceptions of compassion, practising compassion and the infrastructure to support compassion are discussed. Implications for Nursing It is anticipated that this discussion will prompt further debate, raise awareness and help to clarify the meaning of compassion in everyday practice with patients, relatives and staff, so that it can be more clearly named, valued and defended. Conclusion This article challenges some of the beliefs and values that underpin the meaning of compassionate care and its application to practice. It brings greater clarity to the meaning of compassion, which could be used to form the basis of shared visions of caring, both strategic and operational, across organizations.